Dental implants in head and neck cancer patients: factors associated with osteoradionecrosis and implant failure in a retrospective cohort - Vihervaara, Vihtori (My University, 2026)
Background Rehabilitation with dental implants after head and neck cancer treatment is clinically demanding, as previous radiotherapy, reconstructive procedures, and local tissue conditions may impair healing. Osteoradionecrosis (ORN) is among the most serious late adverse events in this setting, yet its relationship with implant treatment, implant-specific local radiation dose, and reconstructed versus native bone has not been fully clarified. Methods This retrospective cohort study included 140 head and neck cancer patients treated with dental implants at Turku University Hospital, Finland, between 2005 and 2024. Demographic, oncologic, surgical, and radiologic data were abstracted from electronic health records. The main outcomes were ORN and implant failure. Baseline characteristics were summarized at the patient level. To avoid non-independence, only one index implant per patient was included in the analyses. Because not all variables were fully documented in all records, analysis-specific denominators were used. Associations between categorical variables were examined with Pearson’s chi-square test or Fisher’s exact test when appropriate, whereas radiation dose was compared between groups using the Mann-Whitney U test. Odds ratios (ORs) with 95% confidence intervals (CIs) are reported when estimable. Results ORN occurred in 6/140 patients (4.3%). All ORN cases occurred in patients who received at least 60 Gy to the implant site (9.5% vs 0.0% for <60 Gy, p = 0.007). Among irradiated patients, the median radiation dose was higher in those who developed ORN than in those who did not (66 Gy vs 50 Gy, p = 0.004). ORN was more frequent in fibula grafts than in native bone (21.1% vs 1.8%; OR 14.93, 95% CI 2.52–88.63; p = 0.004). Implant failure was associated with a two-stage protocol (61.0% vs 42.9%; OR 2.09, 95% CI 1.06–4.11; p = 0.032). Concurrent chemotherapy was not significantly associated with implant failure (p = 0.066). Exploratory secondary analyses did not demonstrate clear associations with post-treatment xerostomia or anatomic localization of the implant. Conclusions In this cohort, high radiation dose and fibula graft reconstruction were strongly associated with ORN, and a two-stage protocol was associated with implant failure. These findings underline the importance of individualized patient selection and incorporating planned implant-specific radiation exposure into treatment planning when considering implant rehabilitation in irradiated or reconstructed jaws.